Minimal Change Disease and Focal Segmental Glomerulosclerosis Are Associated with Good Kidney Prognosis and Thrombotic Microangiopathy with Poor Kidney Survival in Patients with COVID-19-Associated Nephropathies - Neves, Precil Diego Miranda De Menezes; Araújo, Stanley Almeida; Wanderley, David Campos; Sodré, Andressa Monteiro; Campos, Marcos Adriano Garcia [UNESP]; Watanabe, Elieser Hitoshi; Malheiros, Denise Maria Avancini Costa; Cavalcante, Lívia Barreira; Ledesma, Felipe Lourenço; Israel, Karla Cristina Petruccelli; Barcelos, Flávia Lara; Pinho, Laila Lopes De Farias; et al. (Karger Publishers, 2024)
Introduction: The kidney is a frequent target of SARS-CoV-2, potentially developing lesions in glomeruli, vessels, and tubulointerstitium in response to this infection. Herein, we present the analysis of the first large Latin American cohort of adult patients undergoing kidney biopsy due to COVID- 19-associated kidney disorders. Methods: This retrospective, multicenter, national study was based on the collection of information on demographics, comorbidities, laboratory data, kidney histology, therapy, and therapeutic response. Patients diagnosed with collapsing glomerulopathy (CG) were genotyped for APOL1. Results: Our cohort included 94 patients, most male (62.8%). The median age was 44 (33-52) years, and 50% of them were previously hypertensive. The time between COVID-19 diagnosis and kidney biopsy was 30 (15-60) days. Most patients had decreased kidney function at diagnosis, 43.5% required dialysis upon diagnosis, 77.6% received immunosuppression, and 2/3 achieved a clinical remission. CG was the most common kidney involvement (18 cases), reproducing previous findings. Focal segmental glomerulosclerosis (FSGS), thrombotic microangiopathy (TMA), and IgA nephropathy were also frequent, with 10 cases each. FSGS and minimal change disease (MCD) were associated with the best cumulative kidney survival; none started dialysis. In contrast, patients with TMA/C3 glomerulopathy presented a poor kidney prognosis, with more than half progressing to kidney replacement therapy. Conclusion: A novel and striking finding of our study, therefore, was the association of FSGS and MCD with the best kidney outcome among all COVID-19-related histological patterns. Moreover, the overall distribution of histological profiles showed significant particularities in the analyzed patient cohort, the most important being the higher frequency of TMA cases.
Keywords: COVID-19; Kidney pathology; Kidney prognosis; Podocytopathies; SARS-CoV-2; Thrombotic microangiopathy